Rancang Bangun Aplikasi Sistem Pakar Diagnosis Penyakit Jantung: Studi Kasus pada Klinik Siaga Menggunakan Metode Case-Based Reasoning (CBR) Berbasis Web - Agustinus Manek; Widyat Nurcahyo; NM Faizah (Design Journal, 2024)
In the era of modernization, technological advancements are developing rapidly and play an essential role in various aspects of life, including healthcare. Technology enables people to easily access information in fields such as business, education, and health. In the medical field, computer-based expert systems assist professionals in diagnosing diseases and solving specific problems. This study focuses on developing an expert system application for diagnosing heart diseases using the Case-Based Reasoning (CBR) method, implemented as a web-based system with PHP and MySQL. The heart, a vital organ responsible for pumping blood, is slightly larger than a fist (around 200–425 grams). According to Dr. Helmanu Kurniadi and Ulfa Nurrahmani, S.Kep., smoking is identified as one of the contributing factors to heart disease. The developed application consists of five primary elements, with several menus such as the homepage, user data, disease information, disease list, and login page. Based on black box testing, the application has been thoroughly tested to ensure it functions correctly and is free from coding errors. Additionally, acceptance testing was conducted eight times, resulting in a 100% accuracy rate, aligning with the intended design. Thus, the application is ready to be deployed and is expected to assist both the public and healthcare professionals in diagnosing heart diseases effectively.